2015
DOI: 10.1590/0104-6632.20150324s00003547
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Semicontinuous Reaction Systems for High-Solids Enzymatic Hydrolysis of Lignocellulosics

Abstract: -An attractive operation strategy for the enzymatic hydrolysis of lignocellulosics results from dividing the process into three stages with complementary goals: continuous enzyme adsorption at low-solids loading (5% w/w) with recycling of the liquid phase; continuous liquefaction at high-solids content (up to 20% w/w); and, finally, continuous or semicontinuous hydrolysis with supplementation of fresh enzymes. This paper presents a detailed modeling and simulation framework for the aforementioned operation str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…The two step enzyme saccharification increased the reducing sugar due to high sugar concentration which may block further enzyme hydration. It was previously reported that removal of accumulated sugar prevents feedback inhibition experienced in the initial step (Qi et al 2011;Ouyang et al 2013;Quiroga et al 2015).…”
Section: Two-step Enzymatic Saccharification Of High-pressure Steam Pmentioning
confidence: 97%
“…The two step enzyme saccharification increased the reducing sugar due to high sugar concentration which may block further enzyme hydration. It was previously reported that removal of accumulated sugar prevents feedback inhibition experienced in the initial step (Qi et al 2011;Ouyang et al 2013;Quiroga et al 2015).…”
Section: Two-step Enzymatic Saccharification Of High-pressure Steam Pmentioning
confidence: 97%
“…The two-step process was based on the optimization of the enzyme adsorption on the biomass during the first short stage of the process (about 1 h) and the successive optimization of extensive hydrolysis during the second, long stage of the process (up to 48 h). A similar strategy was modelled by González Quiroga et al [9]. They proposed a two-step enzymatic hydrolysis at different biomass loadings in different continuous reactors.The further development of the proposed two-step strategies asks for the quantitative characterization of the hydrolysis of cellulose in real biomass.…”
mentioning
confidence: 94%
“…Gusakov et al [7] tested the cellulose conversion in a batch reactor and in a plug-flow reactor to select the best configuration in terms of cellulose conversion. Nowadays, further studies are focused on innovative strategies to combine two fundamental targets: the maximization of both sugar concentration in the hydrolysate and polysaccharides conversion [8,9]. Typically, these two targets are in contrast with one another: high biomass loading (15-20 wt%) favours high soluble sugar concentration and low polysaccharides conversion, and low biomass loading (about 5 wt%) provides low sugar concentration and high polysaccharides conversion.…”
mentioning
confidence: 99%
“…There are a number of indications that enzymatic hydrolysis could benefit from a continuous process partly due to the potential to overcome product inhibitions. It is known that the enzymes used for the saccharification of cellulose are inhibited by the presence of glucose and cellobiose, limiting the possible sugar concentration in the hydrolyzed liquid .…”
Section: Introductionmentioning
confidence: 99%